How government green investment affects the carbon emission reduction process: empirical evidence from prefecture-level cities in China - Pan, Ruoxi; Hu, Yiguo; Xu, Xiangbo; Yuan, Naixiu; Zhou, Kai (Frontiers in Environmental Science, 2023)
Government green investment (GGI) is one of the effective tools for reducing carbon emissions (CEs). This is of great significance for the realization of “carbon peaking and carbon neutrality.” This study innovatively considers the multidimensional CE reduction (CER) process indexes to explore the impact mechanism of GGI on China’s CER process. At the same time, CER is particularly critical in resource-dependent regions. This study incorporates this perspective to explore the CER effect of GGI in these regions. This paper developed a multidimensional evaluation system for China’s CER process, using panel data of 269 prefecture-level cities from 2008 to 2019 to explore the impact of GGI on China’s CER process. The results indicated that 1) GGI promotes CER in China as a whole and effectively inhibits CEs, per capita CEs, and CE intensity; 2) GGI promotes CER to some extent by enhancing the energy efficiency and total factor productivity; 3) it plays a larger role in CER in regions with a high energy endowment; and 4) the impact of GGI on CER is heterogeneous in geographical regions, city sizes, and economic development levels. This study makes policy recommendations for reducing CEs, including intensifying GGI and playing its investment-pulling role, thereby increasing the investment related to improving energy efficiency and total factor productivity and promoting government intervention in areas with high energy endowments.